Career Adaptability and Work Volition among Aviation Vocational Cadets: The Mediating Role of Career Engagement toward SDG 4, SDG 8, SDG 9, and SDG 10 - Linda Winiasri; Ekohariadi Ekohariadi; Ratna Suhartini (Journal of Current Studies in SDGs, 2026)
Objective: To analyzes the direct effect of career adaptability on work volition among cadets in aviation vocational higher education and its indirect effect through career engagement, while positioning the model within the Sustainable Development Goals (SDGs), especially SDG 4, SDG 8, SDG 9, and SDG 10. Method: The study used a quantitative explanatory design involving 310 active non-Polbit Diploma III cadets from Politeknik Penerbangan Surabaya and Akademi Penerbang Indonesia Banyuwangi. Data were collected using a closed-ended questionnaire with a six-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).  Results:  Career adaptability had a positive and significant effect on career engagement, career engagement had a positive and significant effect on work volition, and career adaptability had a positive and significant direct effect on work volition. Career engagement also significantly mediated the relationship between career adaptability and work volition, indicating partial mediation. Novelty: The study contributes to SDG-oriented aviation vocational higher education by explaining how adaptive career resources become a perceived capacity for occupational choice when translated into proactive career development behavior among non-Polbit cadets.